An isolated palmar scaphoid dislocation with undisplaced fracture: A case report and review of literature - Hegde, Atmananda; John, Davis; Kamath, Surendra U; Sera, Rakesh; L K, Sunil (Indian Journal of Case Reports, 2018)
Isolated carpal scaphoid dislocation is an extremely uncommon injury. Various methods have been used to treat the scaphoiddislocations, which involves open reduction and K-wire fixation with or without ligament repair or just closed reduction andcast application. The rarity of this injury has led to the proposal of vague and sometimes conflicting treatment strategies. In thisarticle, we report a case of isolated palmar dislocation of scaphoid with an undisplaced fracture. Even though isolated dislocationsof scaphoid have been reported before, this particular injury pattern of isolated dislocation with a fracture through the waist ofscaphoid has not been reported before to the best of our knowledge. This case was managed by closed reduction, percutaneousHerbert screw fixation, and cast immobilization for 6 weeks, which produced a satisfactory short-term outcome.